Agama dan Negara: Konstruksi Agama sebagai Fenomena Marginalisasi Kepercayaan Lokal Minahasa Sulawesi Utara - Mandey, Geiby Natalia; Pinatik, Hun (LP2M UIN Sunan Kalijaga, 2022)
This study explores the relationship between religion and the state which has an impact on the marginalization of local beliefs as a natural thing. The term